Mounding technique improves physiological performance and yield of oil palm on Spodosols - Suwardi, Suwardi; Sutiarso, Lilik; Wirianata, Herry; Nugroho, Andri Prima; Pradiko, Iput; Ginting, Eko Noviandi; Darlan, Nuzul Hijri; Syarovy, Muhdan; Primananda, Septa; Sukarman, Sukarman (Universitas Sebelas Maret, 2022)
Spodosols have been widely used for oil palm plantations, specifically in Kalimantan, Indonesia. However, they are sub-optimal for agriculture due to a lack of water and nutrient-holding capacity and a spodic layer that limits plant root development. Therefore, proper agriculture practices are needed for oil palm to enhance its potential yield. This study aims to determine the effect of the mounding technique on the physiological performance and yield of oil palms in spodosol. The study location was well-managed, with eight blocks of oil palm plantations planted in 2008 on spodosols (Typic Haplohumod) in Central Kalimantan. The mounding technique was applied to four blocks of oil palm planted in 2015, while the remaining four were left without mounding. The parameters observed were soil moisture, transpiration, number of bunches, bunch weight, and yield. The results showed that the average moisture in the mounded soil was 4% greater than the control. Additionally, the average daily transpiration of oil palm with the mounding was up to 2.30 mm day-1 or three times higher than the control. The implication was that the average yield of oil palm increased from approximately 1.84 to 3.71 tons ha-1 year-1 compared to no-mounding treatments. Furthermore, the average yield was 19-66% higher than the block without the mounding application.